2003
DOI: 10.1542/peds.111.3.e248
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Generalized Joint Hypermobility With and Without Musculoskeletal Complaints: A Localized or Systemic Disorder?

Abstract: ABSTRACT. Objectives. Children with generalized hypermobility of the joints and musculoskeletal complaints frequently visit pediatric clinics, but many show no currently known collagen or other possibly related diseases. Whether the symptoms are confined to the musculoskeletal system is unknown. We assessed whether such children have detectable differences in laxity of connective tissue present in organ systems other than joints. We also assessed whether children with generalized joint hypermobility and muscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 31 publications
3
78
1
2
Order By: Relevance
“…Our results agree also with Engelbert et al, 2003 [21], when he said that, Children with generalized joint hypermobility without musculoskeletal complaints had significantly higher total range of joint motion, and lower total muscle strength as compared with the reference group when they use hand-held myometer in the assessment. However, some of their findings may point towards another explanation, that these children are less active than normal children which also concluded by Dolan AL, 1998 [22].…”
Section: Discussionsupporting
confidence: 92%
“…Our results agree also with Engelbert et al, 2003 [21], when he said that, Children with generalized joint hypermobility without musculoskeletal complaints had significantly higher total range of joint motion, and lower total muscle strength as compared with the reference group when they use hand-held myometer in the assessment. However, some of their findings may point towards another explanation, that these children are less active than normal children which also concluded by Dolan AL, 1998 [22].…”
Section: Discussionsupporting
confidence: 92%
“…dancers) and symptomatic forms of GJH (e.g. EDS-HT, hypermobility syndrome) [19][20][21] In these studies, muscle weakness was found to be associated with pain [22] and fatigue. [21] However, whether these factors moderate the association between muscle strength and activity limitations is unknown.…”
Section: Introductionmentioning
confidence: 94%
“…[33] The HAQ disability index ranges from 0 to 3, where scores of 0 -1 represent mild to moderate disability, 1-2 moderate to severe disability, and 2-3 severe to very severe disability. [33] Musculoskeletal function Muscle strength in both extremities was measured bilaterally in a standardized way [19] with a hand-held dynamometer (Citec, Groningen, The Netherlands). Measurements were consecutively performed three times and the highest value was registered.…”
Section: Activity Limitationsmentioning
confidence: 99%
“…However, the risk of having (ankle) injuries due to larger sway for the GJH group must be studied in future longitudinal studies. J Orthop Sports Phys Ther 2017;47 (10) …”
Section: U T Conclusion: For Ballet Dancers and Teamgymmentioning
confidence: 99%
“…Additional reasons for sustaining an injury may be decreased muscle strength and consequent decreased muscular stability, as confirmed in some studies of 8-to-10-year-old children with symptomatic GJH 10 and in the general adolescent athlete, 3 but not in studies of children with nonsymptomatic GJH. 22 However, motor performance has never been studied in elite-level adolescent athletes with GJH.…”
mentioning
confidence: 96%